A GLANCE AT THE LIFE AND LEGACY OF GURU PADMASAMBHAVA - Wangmo, Kalsang; M. Ramakrishnan (International Journal of Research -GRANTHAALAYAH, 2025)
Popularly known as Guru Rinpoche, or the "Second Buddha", Guru Padmasambhava was a well-revered tantric Buddhist master from medieval India, and he taught Vajrayana in Tibet circa the 8th – 9th century and helped construct the first Buddhist monastery in Tibet (Samye Monastery). He played a significant role in the transmission of Buddhism to Tibet and in the Himalayas which is considered most remarkable, and likewise, he has also been regarded as one of the main architects of the Guru Padmasambhava mythos simply because of his activities that had tamed the Tibetan spirits and demigods. The modern Tibetans consider him a Buddha as Buddha Shakyamuni foretold it, and the Guru Padmasambhava narrative emerged during the eleventh and twelfth centuries, among narratives on others, resulting in the projection of him as one of the most influential legends with reference to the Buddhist tradition in Tibet. Different stories are associated with the birth of Guru Padmasambhava and all of them have their own logic and interpretations, and as the versions of these stories are not contradictory to themselves, they depict the perfect understanding of the sentiment or belief that “everything is flexible, anything is possible. Enlightened beings can appear in any way they want or need to.” Similarly, Guru Padmasambhava has eight manifestations and all of them have both philosophical appeal and epistemological content. His attributes are highly philosophical and relevant in the modern context, and this interdisciplinary reading of those attributes offers new insights into the existential necessities of his thoughts for the present generation. Taking the statement of Guru Padmasambhava that “My father is wisdom and my mother is voidness / My country is the country of Dharma / I am of no caste and no creed / I am sustained by perplexity; and I am here to destroy lust, anger and sloth”, as the first step, this paper attempts to unravel the philosophical underpinnings of his life and legacy.